The study of oral anti-diabetic drugs utilization at outpatient department of Hospital Tengku Ampuan Rahimah; a cross sectional study / Nurul Asikin Nasir - Nasir, Nurul Asikin (2014)
This study was mainly designed to determine drug use pattern of oral anti-diabetic medications among patients with type 2 diabetes mellitus and to compare drug and dose of oral anti-diabetics drugs prescribed to adults and geriatric patients. A retrospective cross sectional quantitative descriptive study had investigated by involving ambulatory patients of Hospital Tengku Arnpuan Rahimah with confirmed with Type 2 Diabetes Mellitus. 2893 of 9927 prescriptions from November 2013 had been selected and 291 patients had used oral anti-diabetic medications. Half of diabetic patients had prescribed with metformin. Only 3% patients had prescribed anti-diabetic medication out the recommended dose. Almost all (97%) physicians follow the Malaysian's Clinical Practice Guideline in term of dose of anti-diabetic medications. There is not much difference in drug prescribing pattern among adult and geriatric patients.However, physicians do not follow the Malaysian's clinical practice guideline in prescribing of glibenclamide to geriatric patients. It can lead to hypoglycemic episodes. As an conclusion, majority of physicians of Hospital Tengku Arnpuan Rahimah (HTAR) had followed the guideline in giving the best pharmaceutical care to patients